Discrimination and Socially Embedded Suffering: Extending Grant’s Critique of Track 2 MAID to Mental Illness - Dunn, Nicholas (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
In her paper entitled “Why Track 2 MAiD is Discriminatory,” Isabel Grant offers a compelling disability justice-based critique of Canada’s evolving MAID regime. She argues that Track 2 MAID, which concerns persons who are not approaching the end of life, is premised on a medical model of disability that obscures structural ableism and therefore discriminates against persons with disabilities. In this commentary, I show that Grant’s analysis becomes even more urgent when extended to current debates about the expansion of MAID eligibility for individuals with mental illness as the sole underlying medical condition.